Measurement of the absolute branching fraction of Ds+ --> tau+ nutau decay. - Ecklund, K; Love, W; Savinov, V; Lopez, A; Mendez, H; Ramirez, J; Ge, J; Miller, D; Shipsey, I; Xin, B; Adams, G; Anderson, M; et al. (2008)
Using a sample of tagged D(s)(+) decays collected near the D(s)(*+/-)D(s)(-/+) peak production energy in e(+)e(-) collisions with the CLEO-c detector, we study the leptonic decay D(s)(+)-->tau(+)nu(tau) via the decay channel tau(+)-->e(+)nu(e)nu(tau). We measure B(D(s)(+)-->tau(+)nu(tau))=(6.17+/-0.71+/-0.34)%, where the first error is statistical and the second systematic. Combining this result with our measurements of D(s)(+)-->mu(+)nu(mu) and D(s)(+)-->tau(+)nu(tau) (via tau(+)-->pi(+)nu(tau)), we determine f(D(s))=(274+/-10+/-5) MeV.